FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PEGAWAI SEKRETARIAT JENDERAL SENAT KAMBOJA - Song Sokphearath; Andi Sularso; Siti Komariyah (RELASI : JURNAL EKONOMI, 2014)
The purpose of this research is to know and analyze the influence of employee training, employee attitudes, employee communication skills and organization culture and analyze the factor dominate influence on the employee’s performance of the Secretariat General of the Senate Cambodia. The population of this study were all employees from three General of the Department of the Secretariat General of the Senate Cambodia, amounted to 744 people and anamounted sample of 150 people, by using multiple regression analysis. The technique of data collection used were interviews and observation. The result of this study show that significant influence of variable employee’s training, employee’s attitudes, employee’s communication skills and organization culture on the employee’s performance and variable attitude is the most dominant influence on the employee’s performance.